Comments on two questionably new axiidean taxa from the Gulf of Mexico (Crustacea: Decapoda) - Felder, Darryl L.; Dworschak, Peter C. (Zootaxa, 2015)
A recent descriptive account based on material in the Senckenberg Forschungsinstitut und Naturmuseum included descriptions of two new fossorial axiidean shrimp from the northeastern Gulf of Mexico. Both were based on fragmentary immature specimens, and the accompanying illustrations appeared to potentially represent known species. The types were obtained on loan for study in each of our labs. In one case we conclude that erroneous interpretations of a mangled immature specimen of Axianassa arenaria Kensley & Heard, 1990, led to its assignment to the wrong infraorder, and thus its erroneous description as a new genus and species. In the second case, misinterpretations of morphology of four fragmentary juvenile specimens led to assignment of a name for a population already known in literature to be separated genetically and developmentally from Atlantic populations of Callichirus major (Say, 1818) and Gulf of Mexico populations of C. islagrande (Schmitt, 1935). While no diagnostic characters of value were furnished with the description, we nonetheless conclude that the new name must be used.